Meaning of Marriage Tradition as Local Wisdom of The Malay Community in Seranggam Village Selakau Distric Sambas Regency - Chalimi, Ika Rahmatika; Julia, Julia (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research aims to describe the Marriage Tradition of the Malay Community as Local Wisdom in Seranggam Village. This research used etnography research method. Interviews, observation and documentation have become the data-collection technique used. The marriage tradition of the Malay community in Seranggam Village is a custom that has been carried out by the community from generation to generation. There are three stages that the community goes through in the implementation of this marriage. The first stage that must be passed is before the marriage which begins with the implementation of bepari-pari, asking, then continues with cikram, but the stages before the marriage are not only finished there but are connected again with the implementation of the antar pinang. After that, followed by the procession of the akad nikah, the bride and groom went through the bepallam, bekasai, betangas and beinai processes. The stages that will be followed will be continued after the wedding, namely starting from between pakatan, hari besar or wedding party which is completed with the reading of the al-bazanji book, arak-arakan pengantin, duduk timbangan, makan saprahan, balik tikar filled with belulus bath activities and the last menjalankan pengantin. Each stage has its own meaning in it and the values contained in this wedding tradition are religious and cooperation values.